Interactions between bovine neutrophils and Streptococcus uberis - Syer, Kristy M. (2011)
Streptococcus uberis is a leading cause of mastitis worldwide with significant financial and welfare implications. It is uncontrolled by present disease control strategies and further knowledge of the interactions between host and pathogen are crucial to permit the development of novel control strategies. Neutrophils (PMNs) migrate into the udder in large number and they are responsible for removing other udder pathogens. However previous work has shown that virulent S. uberis 0140J releases an unidentified soluble factor that inhibits the bactericidal activity of PMNs. This work set out to elucidate a better understanding of this host-pathogen interaction; firstly by investigation to determine whether avirulent strains of S. uberis were killed by PMNs, and secondly by assessing transcriptional changes between PMNs after exposure to milk and milk in which S. uberis has been cultured by microarray analysis. Naturally occurring and mutant strains of S. uberis that show attenuation in the host were unaffected by the presence of functional PMNs, indicating that their attenuation in the host cannot be attributed to increased susceptibility to the bactericidal activities of PMNs. PMNs incubated in milk in which S. uberis 0140J had been cultured (ST PMNs) had an altered transcriptome compared to PMNs incubated in milk. Genes involved in cell death and the inflammatory responses appear effected. A down-regulation of pro-apoptotic genes was observed, this finding was supported by a highly significant reduction in the presence of apoptotic cells, compared to cells incubated in milk. Transcription of pro-inflammatory cytokines including CXCL8, IL12β and CCL20 was up-regulated in ST PMNs and genes involved in cellular structure and metabolism had altered levels of expression. This data from this investigation has provided an initial insight into the mechanisms by which S. uberis may elicit changes in PMNs that may relate to inhibition the bactericidal function and/or other host pathogen interactions.